A Stable Nanocobalt Catalyst with Highly Dispersed CoNx Active Sites for the Selective Dehydrogenation of Formic Acid. Issue 52 (30th November 2017) - Tang, Conghui; Surkus, Annette‐Enrica; Chen, Feng; Pohl, Marga‐Martina; Agostini, Giovanni; Schneider, Matthias; Junge, Henrik; Beller, Matthias
Abstract: Novel nanostructured catalysts with highly dispersed cobalt have been synthesized by the pyrolysis of metal phenanthroline complexes. Materials with significantly different properties were obtained by simply tuning the metal/ligand ratio. The catalytic potential of this class of compounds is shown by the first example of the dehydrogenation of formic acid under the catalysis of atomically dispersed cobalt. From TEM, XPS, and XRD characterization, KSCN poisoning, and acid leaching, the formation of CoNx species as the active site seems key to the success of this reaction. Excellent stability and recyclability make this new catalyst also attractive for other applications. Abstract : More efficient on their own : Atomically dispersed cobalt catalysts with excellent recyclability were developed for the dehydrogenation of formic acid (see picture). By tuning the metal/ligand ratio of the catalyst precursor, the structure of the heterogeneous material could be changed from nanoparticles to highly dispersed metal centers. Experimental results show the presence of CoN x species as the active sites.